Religious Radicalization in Swat (2001-2010): Political Perspective - Haider, Abeera; Warraich, Saqib Khan (Annals of Human and Social Sciences, 2025)
Swat valley is in rift of religious radicalization after 9/11. To find the root cause of religious radicalization in Swat after 9/11 researcher holds that poor governance, political instability and weak administration were the main causes. Tehreek-e-Taliban Pakistan (TTP) and Tehrik-e-Nifaz-e-Shariat-e-Muhammadi (TNSM) took advantage of this political vacuum and establish parallel political structures. Rotberg’s ‘Failed State Theory’ is applied because nations fall when they are unable to fulfill fundamental duties of governance. It includes maintaining political stability, law enforcement, and security. The study finds that Pakistani government was more prone to military operations like Rah-e-Rast than to address the root cause of religious radicalization in Swat. Furthermore, religious scholars remained silent to terrorism and denounce only selective acts of radical groups. Thus allows the radical and extremist narratives to thrive. Conflict-prone areas like Swat needs a comprehensive governance approach to restore political stability and cure radical approach.